Different Phenotypes at Onset in Neuromyelitis Optica Spectrum Disorder Patients with Aquaporin-4 Autoimmunity - Long, Youming; Liang, Junyan; Wu, Linzhan; Lin, Shaopeng; Gao, Cong; Chen, Xiaohui; Qiu, Wei; Yang, Yu; Zheng, Xueping; Yang, Ning; Gao, Min; Chen, Yaotang; et al. (Frontiers in Neurology, 2017)
Background: Although rare, brain abnormalities without optic neuritis (ON) or transverse myelitis (TM) diagnosed with neuromyelitis optica spectrum disorder (NMOSD) have been reported in patients positive for the aquaporin-4 (AQP4) antibody. Objective: To analyze demographic and clinical differences among NMOSD patients without ON or TM, those with either ON or TM, and patients with simultaneous ON and TM at disease onset. Methods: In this retrospective study, patients were recruited who were positive for the AQP4 antibody, as detected using a cell-based assay, at the Second Affiliated Hospital of Guangzhou Medical University in China. Demographic and clinical data were obtained from each patient’s medical record. Results: A total of 292 patients were included in this study and were divided into four subgroups based on their initial manifestations: (i) NMOSD without ON or TM (NMOSD-ON-TM-, n = 70); (ii) NMOSD with ON (NMOSD-ON+, n = 95); (iii) NMOSD with TM (NMOSD-TM+, n = 116); and (iv) simultaneous ON and TM (NMO, n = 11). We found that age at onset was lower in the NMOSD-ON-TM- group than that in the other groups. The interval from the first episode to relapse was shorter in the NMOSD-ON-TM- group than that in NMOSD-TM+ group. Cerebral spinal fluid white cell counts and protein levels were significantly higher in the NMOSD-ON-TM- group than those in the other groups. Lower EDSS scores were observed in the NMOSD-ON-TM- group. Brain abnormalities, including in area postrema and hemisphere lesions, were more frequent in the NMOSD-ON-TM- group. Kaplan–Meier analysis showed that patients in the NMOSD-ON-TM- group experienced earlier relapse than those in other groups. Conversion to NMO in the NMOSD-ON+ group was greater than that in the other groups. Only 14 patients (4.8%, 14/292) had pure brain abnormalities, of which 12 had disease duration of several more years and eight (57.1%) experienced relapses. Conclusions: NMOSD patients with different initial manifestations present with significant differences in clinical features during follow-up. Patients with long-term AQP4 autoimmunity in the brain in the absence of ON or TM are not common.